Progress on the Biological Activities of Helicid and its Derivatives - Xia, Xi; Cao, Ting-Ting; Li, Yong; Chen, Yu; Yang, Hong-Jun; Zhao, Zhi-Gang; Yin, Shu-Fan (Current Organic Chemistry, 2019)
Helicid is a specific Chinese natural drug. Helicid, its congeners, and its derivatives exhibit pronounced biological activities, among which its hypnotic effects stand out. The well-documented sedation and analgesic activity and low side effects of helicid have drawn more and more attention from scientists. Moreover, its clinical success and intriguing mechanism of action have stimulated great interest in further modification of helicid for improving its hypnotic activity. The 4-formyl group has been a major target for structural derivatization aimed at either producing more potent compounds or overcoming drug disadvantages. Accordingly, numerous helicid derivatives have been prepared via molecular docking and hemisynthesis. Although neither systematic nor comprehensive, there are two excellent reviews on the distribution, sources, applications, synthesis, and pharmacological activity of helicid that have been published in Chinese. In the present review, we attempt to compile and discuss the key data available in the literature on the multiple biological activities of helicid derivatives. This compilation of 102 references may be helpful in understanding the diverse biological properties of helicid while providing insights into its mechanism of action. This may direct future research in the synthesis of new derivatives and the exploration of other biological activities.
Keywords: BuChE and tyrosinase inhibitors